Trans and diverse gender population: access to health services in Brazil (Research, Society and Development, 2021)
Introduction and Objective: When observing the context of discrimination and violence experienced by the transexual population in Brazil, main victim by intentional violent death, this study aimed to analyze the obstacles lived by the transexual population on the access to healthcare services in Brazil. Methodology: It is an integrative review based on the guiding question “what are the obstacles faced by the transexual population on the access to healthcare services in Brazil?” which was made by the PICo strategy to select the indexed descriptors and their respective synonyms, which were combined by the boolean operators to make the search expression. The research was realized, in April 2021, in the data bases of Latin American and Caribbean Health Science Information Center (LILACS), Medical Literature Analysis and Retrieval System Online (Medline) and Excerpta Medica Database (Embase), considering pre-established criteria. Results: Nine publications were selected for full reading and addressed the historical aspects of political and social achievements, in addition to analyzing the current context still permeated by stigma, prejudice, lack of professional qualification and equal access to procedures for body modification. Conclusions: Thus, it was possible to verify advances in the health rights of this population, as a reflection of the institution of the Transsexualizing Process and the National Comprehensive Health Policy for Lesbians, Gays, Bisexuals, Transvestites and Transsexuals. However, these are insufficient to end the inequalities of access generated by discrimination, in addition to not meeting all the specific demands of this group, such as sex reassignment surgeries and hormone therapies.